Attractiveness and Cooperation in Social Exchange - Chisato Takahashi; Toshio Yamagishi; Shigehito Tanida; Toko Kiyonari; Satoshi Kanazawa (Evolutionary Psychology, 2006)
We tested the hypothesis that physically more attractive men are less likely to cooperate in social exchange than less attractive men, while physical attractiveness has no effect on women's tendency toward cooperation, with four different experimental games (Prisoner's Dilemma with 99 players, Allocator Choice with 77 players, Faith with 16 players, and Trust with 21 players). Pictures of the game players were taken after they participated in one of the four games, and those pictures were presented to another set of participants (85 raters in Study 1 and 2, 36 raters in Study 3) for attractiveness ratings. Both male and female raters who were unaware of the photographed game players' actual behavior in the game judged the faces of male defectors (who defected in one of the four games) to be more attractive than those of male cooperators, but they did not give differential attractiveness ratings to female defectors and female cooperators.